Komunikasi Olahraga Antara Pelatih dan Atlet terhadap Performa Atlet di Klub Dayung Sunan Kalijaga Kabupaten Demak - fatah, muhammad syaifullah; Farida, Lulu April (Indonesian Journal for Physical Education and Sport, 2023)
The Sunan Kalijaga rowing club is one of the rowing clubs in Demak Regency, where aspects related to sports communication are not yet known. This study aims to determine aspects related to sports communication between coaches and athletes in improving the performance of athletes.This study uses a qualitative descriptive method that aims to describe the facts and characteristics of a field in a systematic, honest and accurate manner by describing phenomena and conditions in the field. The conclusion from this research is that in improving athlete performance there are three aspects, the most important is interpersonal communication, because a good relationship will make the coach know better what the athlete is like and the athlete can also understand the coach. But it must also be balanced with ideational communication as ideas or knowledge needed in the training process, as well as textual communication so that the language used to convey messages can be more easily received. These three aspects must be fulfilled properly because these three aspects are interrelated with one another.